ANALISIS IMPLEMENTASI PEMBELAJARAN DARING PADA SISWA KELAS V SEKOLAH DASAR BETHEL SINTANG TAHUN PELAJARAN 2020/2021 - Anatasia Anatasia; Adriana Gandasari; Imanuel Sairo Awang (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2021)
This study aims to identify and describe the implementation of online learning in fifth grade students of Bethel Elementary School. This type of research is a qualitative research whose results are described, the study consists of 5 people, 4 students and 1 class teacher. Data collection techniques using direct observation techniques, direct communication techniques, and documentation techniques. Data collection tools in the form of observation sheets, interview sheets, field notes, and documentation. The data analysis technique uses Miles and Huberman analysis techniques through data collection, data reduction, data display, and conclusions. The validity of the data using source triangulation and technical triangulation. The results of the study show that: 1) the implementation of online learning for students includes three stages: a) through planning, namely compiling the syllabus and lesson plans regarding the material to be delivered through online learning, b) implementation of the preliminary, core, and closing activities by providing motivation, advice, and giving assignments during the online learning process. 2) the impact of the implementation of online learning on students, namely the limited use of the internet and difficulty understanding the material presented by the teacher. The impact for teachers, in preparing for learning is less than optimal and teachers are required to be able to carry out online learning, even though some of these teachers are still lacking in the use of technology. 3) the responses of teachers and students after carrying out online learning, regarding the implementation of online learning that the implementation of online learning is distance learning, can be carried out anywhere, difficulties in using networks, teachers lack mastery in the use of technology, and teachers feel there are limitations in the delivery of the material being taught . In conclusion, the implementation of online learning is learning that is carried out within the network (online) using the Whatsapp application